Doing-It-Ourselves as Teacher Researchers: A Collaborative Action Research Approach for Improving Literacy Support at Home (LEARNing Landscapes, 2015)
This paper describes what a group of teacher researchers learned from conducting an action research project in an urban elementary school serving a multilingual community in the northeastern United States. A key goal of the project was to enhance parents’ and caregivers’ support of students’ literacy development in ways that built on home literacy practices. Teachers’ learning included understanding the importance of true collaboration, responding to parent feedback, and teacher-led professional development.
Keywords: teacher research; action research; literacy development; collaboration; professional development